South to north investment linkages and decent work in Brazil - Patrick Wagner; Damian Raess (LABOUR, 2022)
Over the last 250.167emyears, the BRICs asserted themselves as drivers of globalization. But what does their new-found prominence mean for working conditions at home? Using a novel sub-national database covering outward investment linkages and working conditions in Brazilian municipalities, this study tests whether a direct investment in Europe leads to the introduction of decent working conditions in Brazil. The empirical results provide strong support for the investing-up effect using a mixture of panel data analysis and text analysis. The results suggest that economic integration with high-standard developed countries can act as a powerful mechanism for labor standard improvements in developing countries.
Keywords: 380